The Effective Tax Burden of Companies and on Highly Skilled Manpower: Tax Policy Strategies in a Globalized Economy - Christina Elschner; Lothar Lammersen; Michael Overesch; Robert Schwager (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
Company taxes and taxes on highly skilled labour both influence the attractiveness of a particular region as a location for investment. We measure the effective tax burden on capital investment and on highly qualified labour in 33 locations across Europe and the United States. We then correlate both types of tax burden in order to study the different tax policy strategies applied in different countries. We identify three causes for different strategies: political institutions, preferences for redistribution and equality, and the position in globalisation and growth. Small countries, high growth rates, and federal structure with high tax autonomy stand for countries with lower tax burdens, especially on companies. Large countries, representative democracies with coalitions, and a high preference for redistribution are likely to induce higher tax burdens.
Keywords: H25; H24; H21; 330; effective tax burden; tax policy; company taxation; personal income tax; Unternehmensbesteuerung; Hochqualifizierte Arbeitskräfte; Steuerbelastung; Sozialversicherungsbeitrag; Vergleich; Steuerpolitik; Globalisierung; Welt